Effect of size and amount of lightweight expanded clay aggregate on normal incidence sound absorption coefficient of concrete - Lawanwadeekul, Siwat; Torkittikul, Pincha; Mulinta, Soravich; Khunyotying, Thitima; Tasang, Winai; Bunma, Mattika (Engineering and Applied Science Research, 2023)
This study focused on lightweight expanded clay aggregate (LECA) sizes and quantitatively on concrete’s average incidence sound absorption coefficient. LECA samples were produced in three different sizes, namely, large (20 mm), medium (10 mm), and small (5 mm), and were used as the coarse aggregate replacement for cement in various ratios. All the samples were analyzed for physical properties, mechanical properties, and normal-incidence sound absorption coefficients. The results revealed that samples containing less than 50% LECA replacement passed the standard requirement. Nevertheless, a small LECA with a 100% sample is also intriguing. The normal-incidence sound absorption coefficient was more than ten times higher than that of normal concrete.